Elucidation of possible molecular mechanisms underlying the estrogen-induced disruption of cartilage development in zebrafish larvae. (1st June 2018) - He, Hanliang; Wang, Chunqing; Tang, Qifeng; Yang, Fan; Xu, Youjia
Highlights: Estrogen cause abnormal craniofacial bone development along with craniofacial bone degradation. Estrogen cause ECM, focal adhesion, cell cycle, apoptosis, and bone related signaling pathways were disrupted. Estrogen cause such as collagen encoded gene ( col19a1a, col7a1, col18a1, and col9a3 ), fgf19, tgfbr1, cell cycle genes altered. Abstract: Estrogen can affect the cartilage development of zebrafish; however, the mechanism underlying its effects is not completely understood. Four-day-old zebrafish larvae were treated with 0.8 μM estrogen, the 5 days post fertilization (dpf) zebrafish larvae did not demonstrate obvious abnormalities during development; however, the 6 dpf and 7 dpf larvae exhibited abnormal craniofacial bone development along with craniofacial bone degradation. RNA deep sequencing was performed to elucidate the mechanism involved. Gene Ontology functional and KEGG pathway enrichment analysis of differentially expressed genes (DEGs) showed that the extracellular matrix (ECM), extracellular region, ECM-interaction receptor, focal adhesion, cell cycle, apoptosis, and bone-related signaling pathways were disrupted. In these signaling pathways, the expressions of key genes, such as collagen encoded ( col19a1a, col7a1, col7al, col18a1, and col9a3 ), MAPK signaling pathway ( fgf19, fgf6a ), TGF-beta signaling pathway ( tgfbr1 ), and cell cycle ( cdnk1a ) genes were altered. The qRT-PCR results showed that after treatment with 0.8 μM 17-β estradiol (E2), col19a1a, col7a1, col7al, col18a1, col9a3, fgf6a, cdkn1a were downregulated, and fgf19, tgfr1 were upregulated, which were consistent with deep sequencing analysis. Therefore, the effect of estrogen on cartilage development might occur via multiple mechanisms. The study results demonstrate the mechanism underlying the effect of estrogen on cartilage development.